Vpliv prehodnih elementov in njihovih karbidov na aktivacijsko in vezalno energijo pasti v mikrolegiranih jeklih - Vehovar, Leopold (Kovine zlitine tehnologije, 1997)
The research work is linked with investigations concerned the influence of different traps i. e. substitutialy dissolved transition metals of the IV. and V. period of the Periodic System (Nb, V, Ti and Mo) or their carbides, which play an important role in the strengthening process of the matrix (mechanical properties increased) after thermomechanical treatment. Traps are directly in connection with the process of charging of hydrogen into the scrystal lattice, and particulary with the trap binding or trap activation energy. With the permeation method which makes possible the determination of diffusion constant, was established that Fe-V-C and Fe-Nb have the largest ?$t_lag$? at the temperature combination 298 and 323 K. That behaviour means, that of both sorts of alloys could be expected the greatest activation and binding energy of traps in the form of VCx carbides or substitutialy dissolved Nb-atoms. From diffusion constants calculated trap binding energy (Evp) confirm the assumption of large differences in both energies. In ternary Fe-Me-C systems NbCx carbides show the lowest Evp for hydrogen (-2,42 kJ/mol), but that does not cause a critical concentration of H-atoms at trap sites. For this reason, according to different mechanisms, no nucleation of cracks and growth of macrocracks with their coalescence is possible. The same carbides show the lowest Eap (16.12 kJ/mol) needed for hydrogen to escape from trap sites to normal lattice sites or to the outer surface. Production of steel resistant to hydrogen embrittlement is therefore possible by alloying with Nb or even Mo or Ti, however the excessive amount of elements as Ti or Nb in solid solution is detrimental.
Keywords: jekla; prehodni elementi; vodikova krhkost; difuzija; aktivacijska energija; temperatura